Economic integration : aspects and problems - Streeten, Paul (A. W. Sythoff LeydenNL, 1964)
Reflects on problems raised by the recent approaches to European integration. Examines the degree to which economic progress on different fronts should be 'integrated' in the sense of co-ordinated or 'balaned'.